Engineering communication - Knisely, Charles W.; Knisely, Karin (Cengage Learning, 2015)
A practical how-to book, ENGINEERING COMMUNICATION is more than a guidebook for creating clear, accurate and engaging communication -- it is a complete teaching tool that includes the use of technology to produce dynamic written, oral, and visual communication.